Characterization of the double stranded RNA dependent RNase activity associated with recombinant reverse transcriptases. - Ben-Artzi, H (1992)
An in situ gel assay was applied to the study of double stranded RNA dependent RNase activity associated with reverse transcriptase (RT) of HIV-1 and murine leukemia virus. Polyacrylamide gels containing [32P] RNA/RNA substrate were used for electrophoresis of proteins under denaturing conditions. The proteins were renatured and in situ enzymatic degradation of 32P-RNA/RNA was followed. E. coli RNaseIII, but not E. coli RNaseH, was active in this in situ gel assay, indicating specificity of the assay to RNA/RNA dependent nucleases. Analysis of purified preparations of HIV-1 RT p66/p51 expressed in E. coli demonstrated an RNA/RNA dependent RNase activity comigrating with the large subunit (p66) of the enzyme. In addition, this activity of the RT was often accompanied by a contaminating RNA/RNA dependent RNase, with a molecular weight approximately 30,000 dalton identical to that of E. coli RNaseIII. As the p51 small subunit of HIV-1 RT and a mutant of RT p66/p51, at Glutamic acid #478, did not exhibit RNA/RNA dependent RNase activity, at least part of the active site of the RNA/RNA dependent RNase activity appeared to reside at the carboxy end of the molecule. As these RT proteins are also deficient of RNaseH, our results suggest overlapping or identical catalytic sites for degradation of the substrates RNA/DNA and RNA/RNA.